مقولات الزمخشري النحوية في المغرب على وجهين - أحمد، سعد محمد; صالح، منى نزار (جامعة الموصل - كلية التربية الأساسية, 2019)
The research dealt with the inflected in two aspects in the book of Al-Zamakhshari, which is entitled "the interpretation of the explorer." The importance of the research shows that Imam al-Zamakhshari was asked about a grammatical question, and then he answered the question, which indicates the importance of what he said to : I said, and often his words were controversial in grammar between the grammarians or the problem of expression, and to reveals what is vague and explain what is the problematic, and between the expression and meaning, making the grammatical functions in the statement of meanings of words and Understand. The study required dividing it into preamble and preface and four sections. We summarized in the preface the speech on the concept of expressing the language and terminology and the pluralistic aspects of the narratives and its statements, and then the statement of the narrated in Arabic on two sides. It was divided into four sections and concluded the whole work with a conclusion by summarizing the most important result. And then came the search Sources and references.
تناول البحث دراسة المعرب على وجهين في كتاب الزمخشري الموسوم بـــ (تفسير الكشاف)، وتظهر أهمية البحث في أن الإمام الزمخشري كان يسأل في مسألة نحوية، ثم بعد ذلك يجيب عن السؤال، مما يدل على أهمية ما كان يجيب عنه في النحو بقوله: فإن قُلتُ... قُلْتَ، وغالباً ما تكون مقولاته في مسألة خلافية في النحو بين النحاة أو مسألة مشكلة في الإعراب، ويجيب عن ذلك ويكشف ما هو مبهم ويوضح ما هو مشكل، وكان يربط بين الإعراب والمعنى، إذ جعل الوظائف النحوية في الإبانة عن معاني الكلام ووجوه فهمه. واقتضت الدراسة في هذا البحث تقسيمها على تمهيد وأربعة مطالب، أوجزنا في التمهيد الكلام على مفهوم الإعراب لغة واصطلاحاً وتعدد الأوجه الإعرابية ومقولاته، ومن ثم بيان المقولات المعربة على وجهين وجاءت مقسمة على أربعة مطالب، وخُتم العمل كله بخاتمة أوجزنا فيها أهم النتائج، وأردف البحث بالمصادر والمراجع.
Keywords: اللغة العربية -- النحو العربي -- الزمخشري، محمود بن عمر بن محمد، ت. 538 هـ. -- المغرب